Hand hygiene in hospital environments: use of conformity indicators - Thaíne Cristina Romualdo dos SANTOS; Camila Eugenia ROSEIRA; Thaís Helena PIAI-MORAIS; Rosely Moralez de FIGUEIREDO
An exploratory descriptive study with a quantitative approach whose objective was to use indicators to evaluate the frequency and infrastructure for hand hygiene, as well as the nursing team's knowledge about the subject. Systematized observation was carried out at hospital in the state of São Paulo, Brazil of the routine activities of 33 participating professionals (nurses and technicians) as well as the application of an individual questionnaire about the subject.1206 opportunities for hand hygiene were identified, though it was effected in only 481 (39.9%) of them. Alcohol solution was not used at any opportunity. The infrastructure indicator for hand hygiene was close to the ideal value (83.3%). The professionals reported a high frequency of hand hygiene, demonstrating knowledge in relation to its importance, yet contradicting the findings of the observation. It was concluded that, despite the adequate infrastructure, hand hygiene was below that expected, requiring actions and strategies to overcomes these barrier and increase the use of alcohol solution.